A natural history of lower-risk myelodysplastic syndromes with ring sideroblasts: an analysis of the MDS-CAN registry. Issue 13 (10th November 2022) - Buckstein, Rena; Chodirker, Lisa; Mozessohn, Lee; Yee, Karen W.L; Geddes, Michelle; Zhu, Nancy; Shamy, April; Leitch, Heather A.; Christou, Grace; Banerji, Versha; Brian, Leber; Khalaf, Dina; et al.
Abstract: Patients with lower-risk (LR) myelodysplastic syndromes (MDS) with ring sideroblasts (RS) have better prognosis than those without RS, but how they fare over time is not fully understood. This study's objective was to assess the natural history of LR MDS with RS ≥5% using MDS-CAN registry individual data. Kaplan–Meier estimates and generalized linear mixed models were used to describe time-to-event outcomes and continuous outcomes, respectively. One hundred and thirty-eight patients were enrolled; median times from diagnosis to enrollment and follow-up were 6.6 and 39.6 months, respectively. Within 5 years of enrollment, 65% of patients had ≥1 red blood cell transfusion dependence episode. Within 5 years of diagnosis, 59% developed iron overload, 38% received iron chelation therapy, 14% progressed to acute myeloid leukemia, and 42% died. Patients exhibited inferior health-related quality of life trends. These first real-world data in LR MDS-RS in Canada indicate a high level of morbidity and mortality over a 5-year period. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT02537990